Dictionary Meaning and HistoricalGeographical and Linguistic Interpretation of the Word "Capital" - Baykabilov Khusnudin Mardanovich (Genius Journals, 2023)
The article describes the dictionary meaning and the historical-geographical, linguistic interpretation of the word "capital". The article provides information on the linguistic analysis of the word "city" in different foreign languages and synonyms for the word "capital".
Keywords: Capital; special federal district; city; urban settlements